An evidence-based behavioural intervention on saiga horn as a traditional medicine in Singapore - Doughty, HL (2020)
Illegal and/or unsustainable wildlife trade affects wildlife globally. To address this issue, a plethora of demand reduction efforts have been carried out. However, shortcomings in behaviour change interventions targeting wildlife consumers have been widely noted, and these likely compromise conservationists’ capacities to assess, and stem, unsustainable use of wildlife. In disciplines, such as public health, which include behavioural approaches, behaviour change interventions have been extensively implemented and offer useful insights for addressing wildlife trade. Thus, for this thesis I aimed to design, implement, and evaluate an evidence-based behaviour change intervention that robustly applies relevant approaches found in behavioural science-informed disciplines to the field of wildlife trade. For this work I targeted saiga horn usage in Singapore. The saiga (Saiga tatarica) is a Critically Endangered antelope from Central Asia whose horn is used in traditional Chinese medicine (TCM) to treat fever and heatiness (a TCM state of illness with symptoms like cough). Chapter 2 shows that not only is saiga horn commonly used in Singapore, but that many Chinese Singaporeans consider saiga horn a product option they use most often; and that middle-aged Chinese Singaporean women are among the largest consumers and are the most likely to purchase saiga horn for other people. Perceived efficacy and recommendations from others, are the top stated reasons for using saiga horn. Chapter 3 highlights that there are many interlinked influences affecting saiga horn usage among middle-aged Chinese Singaporean women, and that some of these influences, particularly related to their societal-level perspectives and health information sources, would be important and feasible to leverage in a behaviour change intervention. Chapter 4 details the implementation of a carefully disseminated, socially-framed, online intervention targeting saiga horn usage among middle-aged Chinese Singaporean women. This chapter shows how concepts around repeat message exposure, news spread, and social reinforcement were employed to produce positive immediate online audience response to an intervention message. Chapter 5 reveals how the highly pervasive online intervention resulted in some measurable behavioural impacts on middle-aged Chinese Singaporean women’s usage of saiga horn, as well as impacts on their awareness of saiga antelopes. Though this chapter also discusses heterogeneity in impact, where limitations arose in the intervention, and where relevant future research could improve upon this work. Chapter 6 looks at how this thesis ties with wider discourse around behaviour change interventions in demand reduction, how conservationists can improve this arena, and some potential directions for future research on this study system. In sum, this thesis helps to fill a key gap in our understanding of effective, evidence-based, large-scale approaches that can be feasibly implemented to induce change among unsustainable wildlife trade consumers.